KEDUDUKAN ANAK ANGKAT DALAM HAK WARIS PADA MASYARAKAT ISLAM DI KOTA PALOPO (RELEVANSINYA PADA PENGADILAN AGAMA PALOPO) - Amir, Rahma (PALITA, 2016)
AbstractAccording to the law, Islamic Law Compilation (KHI) is a written law that used as specificguidelines for Muslims in resolving all legal issues including on the status of an adopted child.Therefore, this study aims to: 1). Knowing the position of adopted children with KHI and CivilLaw, 2). Knowing the position of adopted children and their legacy rights. 3). Knowing theposition adopted child and the adoptive parents, their legacy and guardian of the marriage.